Effects of nonparticipation at previous screening rounds on the characteristics of screen-detected breast cancers. Issue 154 (September 2022) - Duijm, Lucien E.M.; Broeders, Mireille J.M.; Setz-Pels, Wikke; van Breest Smallenburg, Vivian; van Beek, Hermen C.; Donkers-van Rossum, Astrid B.; Slob, Marjan J.; Kuipers, Toon P.; Mann, Ritse M.; Voogd, Adri C.
Highlights: A vast majority of women with a screen-detected cancer had a 2-year screening interval between their two latest screens. A slight negative influence on the tumour characteristics and treatment of screen detected cancers was present when the screen interval between the two latest screens was at least six years. Screening mammography especially detects relatively slow growing cancers with more favourable tumour grading characteristics, whereas more aggressive cancers may emerge as interval cancers. Abstract: Purpose: We determined the incidence and effects of different screening intervals prior to a true positive recall on the tumour characteristics of screen-detected cancers (SDC) and interval cancers (ICs) at biennial screening mammography. Methods: A consecutive series of 553020 subsequent screens was included, obtained in a Dutch screening region between January 2009 and July 2019. During 2-year follow-up, we obtained data on radiological procedures, pathology and surgical interventions of all recalled women. Results: A total of 13, 221 women were recalled (2.4% recall rate), yielding 3662 women with a SDC (6.6 SDCs per 1000 screen). Of these, 3477 (94.9%) had attended their two most recent screens as scheduled (i.e., 2-year screening interval), whereas the interval between the two most recent screens was four years or at least six years in respectively 132 (3.6%) and 53 (1.4%) women. There was a trend of higher cancer detection rates in case of longer screening intervals. The proportions of DCIS versus invasive cancer, as well as tumour histology, tumour size, axillary lymph node status, B&R grading, hormone receptor status and type of surgical treatment (breast conserving surgery or mastectomy) were comparable for women with a 2-year or 4-year interval between their two latest screens. SDCs in women with at least six years between their two latest screens were more frequently estrogen receptor negative or triple negative and were more frequently treated by mastectomy. All tumour characteristics mentioned above were less favourable for ICs than SDCs. Conclusions: A vast majority of women with a SDC had a 2-year screening interval between their two latest screens. A screening interval of at least six years had a slight negative influence on the tumour characteristics and treatment of SDCs.